2004
DOI: 10.1002/jms.674
|View full text |Cite
|
Sign up to set email alerts
|

Extraribosomal cyclic tetradepsipeptides beauverolides: profiling and modeling the fragmentation pathways

Abstract: Profiling of cyclic tetradepsipeptides beauverolides was tested as a chemotaxonomic tool for fungal strain identification/discrimination. Two new tetradepsipeptides, beauverolides Q and R, were characterized by tandem mass spectrometry. Specific elimination of 113 atomic mass units from both protonated and sodiated molecules of beauverolides is ubiquitous for all 12 most dominant congeners evaluated in this profiling study. Reconstruction of the total ion chromatogram, according to this neutral fragment releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 56 publications
1
30
0
1
Order By: Relevance
“…are cyclic tetradepsipeptides containing C 9 - or C 11 -β-hydroxy acid residues [32] (Figure 4a). More than twenty different beauverolides have been identified, and sequencing of beauverolides by tandem mass spectrometry has been well described [32], [33]. The product ion mass spectra we obtained in this study were virtually identical to those in the literature.…”
Section: Resultssupporting
confidence: 73%
“…are cyclic tetradepsipeptides containing C 9 - or C 11 -β-hydroxy acid residues [32] (Figure 4a). More than twenty different beauverolides have been identified, and sequencing of beauverolides by tandem mass spectrometry has been well described [32], [33]. The product ion mass spectra we obtained in this study were virtually identical to those in the literature.…”
Section: Resultssupporting
confidence: 73%
“…However, many non-ribosomal cyclic peptides are cyclized via lactone formation and include nonstandard amino acids 53. Theoretical calculations suggested that cyclic peptides favor lactone bond as the initial ring opening site and also the fragmentation pathway of cyclic peptides differs when lactone bond(s) were involved 29. It is therefore important to establish how these other structural features impact the fragmentation data and the results analyzed by the MS-CPA program.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Loss of H 2 O or NH 3 is a common phenomenon found for cyclic peptides, even if no hydroxyl groups are present in the molecule [40], [44], [46], [48], [60][64]. Loss of H 2 O and NH 3 at the same time is possible, and also side chain neutral losses in conjunction with H 2 O or NH 3 losses have been observed [27], [45], [47].…”
Section: Methodsmentioning
confidence: 99%